SIMBOL DAN MAKNA MANTRA PENGOBATAN PADA MASYARAKAT DESA PADANG TIKAR KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA - Ira Yuniar; Antonius Totok Priyadi; Christanto Syam (Universitas Tanjungpura, 2021)
AbstractDescription of symbols and meanings of healing spells in the Padang Tikar Village Community in Kubu Raya Regency. The method used is descriptive. The form of this research is qualitative. The symbol and meaning of the data in this study is a healing spell in the Padang Tikar Village which was spoken by an informant in the Padang Tikar Village, Kubu Raya Regency. The technique of collecting data by means of observation techniques, interview techniques, recording techniques and recording techniques. Based on the data as a whole, the symbols and meanings of medicinal spells in the Padang Tikar village community in Kubu Raya Regency consist of 20 symbols. This research is related to the 2013 curriculum for Indonesian language subjects in grade VII SMP odd semesters which is suggested as a reference for old poetry text material (mantra) for teaching and learning activities in schools. Keywords: symbols and meanings, semiotics, medicinal spells.